AI in microbiome‐related healthcare - Niklas Probul; Zihua Huang; Christina Caroline Saak; Jan Baumbach; Markus List (Microbial Biotechnology)
Abstract Artificial intelligence (AI) has the potential to transform clinical practice and healthcare. Following impressive advancements in fields such as computer vision and medical imaging, AI is poised to drive changes in microbiome‐based healthcare while facing challenges specific to the field. This review describes the state‐of‐the‐art use of AI in microbiome‐related healthcare. It points out limitations across topics such as data handling, AI modelling and safeguarding patient privacy. Furthermore, we indicate how these current shortcomings could be overcome in the future and discuss the influence and opportunities of increasingly complex data on microbiome‐based healthcare.